IMPLEMENTATION OF ROYA PARTIAL OBJECTS OF COLLATERAL RIGHTS AFTER THE APPLICATION OF REGULATION OF THE MINISTER OF AGRARIA AND SPATIAL PLANNING / HEAD OF THE NATIONAL LAND AGENCY OF THE REPUBLIC OF INDONESIA NUMBER 5 YEAR 2020 CONCERNING ELECTRONIC INTEGRATED COLLATERAL RIGHTS SERVICES (Study at Land Office of Malang City) - Sunardi, Sunardi; Suratman, H.; Ali Akbar, Jabbar (International Significance of Notary, 2022)
In this digital era, the Ministry of Agrarian Affairs and Spatial Planning/Head of the National Land Agency seeks to keep abreast of developments by launching electronic services that can be used by Financial Institutions, regarding electronic Mortgage Rights, hereinafter referred to as HT-el, regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of Agency National Land Affairs Number 5 of 2020 concerning Electronic Integrated Mortgage Services which also regulates partial royalties. Article 17 Paragraph (2).Formulation of the problem 1) How to Implement Roya Partial Mortgage Objects Integrated Electronically in the Land Office of Malang City for Creditors and PPAT. 2) What are the Obstacles in the Implementation of Roya Partial Objects of Mortgage Rights Integrated Electronically Faced by Users of Electronic Mortgage Services and Their Settlement Efforts. This research method uses an empirical juridical method with a statutory and sociological approach.The results of research on the Implementation of Roya Partial Mortgage Objects Integrated Electronically in the Land Office of Malang City for Creditors and PPATs are carried out in accordance with regulations. Namely a partial Roya can be done if in the APHT, in which there are several mortgage objects that are guaranteed, a roya agreement (crossing out) is stated for some (partial) mortgage objects whose debt payments have been paid off. The inclusion of this agreement is actually the basis for enacting a partial royalty in the mortgage certificate by the land office. Because if it is not agreed upon, what will apply are the provisions for the implementation of the roya as a whole, as stipulated in Article 2 paragraph (1) of the Mortgage Law, which states: "The mortgage has the nature of not being divided, unless it is agreed in the deed of granting mortgage rights as referred to in paragraph (2).Constraints in the Implementation of Roya Partial Objects of Mortgage Rights Integrated Electronically. Obstacles 1) overlapping rules, 2) the roya process sometimes exceeds 5 working days this is caused by a) high electronic roya submissions, b) lack of public awareness, c) NIK that is not validated, d) unpreparedness from related agencies (ATR BPN) e) system from the ministry which sometimes often errors. The efforts to overcome this are 1) if the guarantee is more than 1 guarantee, it can be used as long as it is promised 2) it is conveyed to the debtor or creditor to take care of the loan as soon as possible 3) For obstacles regarding the readiness of the ATR / BPN Malang City HR, namely by held training and on the implementation of electronic-based Roya Partial, besides that the ministry held improvements to the HT-el and roya HT-el systems. Keywords: Partial Roya, Mortgage-Electronic Rights